THE IMPACT OF ASSISTANCE IN DEVELOPING MICROLEARNING-BASED TEACHING MATERIALS ON THE ENHANCEMENT OF PEDAGOGICAL COMPETENCE AND LITERACY-NUMERACY COMPREHENSION OF GURU PENGGERAK IN KOTA CIMAHI - Dian Maharbid; Riana Irawati; Faridatul A'la; Sani Aryanto; Feni Nur Aisyah; mahda syifa (Universitas Majalengka, 2024)
This research explores the impact of developing microlearning-based teaching materials on enhancing the pedagogical competencies, literacy, and numeracy comprehension of Guru Penggerak in Kota Cimahi. Through a quasi-experimental design with a pre-test and post-test one-group design approach involving pre-tests, post-tests, and the creation of various microlearning formats such as videos, text/images, flashcards, games, and audio podcasts, the study evaluates the effectiveness of these materials in improving instructional practices. The research sample included 50 Guru Penggerak elementary school members from the Komunitas Guru Penggerak Kota Cimahi (KGPKC). The findings reveal significant improvements in pedagogical competencies, particularly in adapting educational materials and providing scaffolding, with an overall increase in average scores from 76.8% to 88%. Literacy and numeracy comprehension also showed positive gains, with literacy increasing from 49.8% to 55.6% and numeracy from 57% to 65%. The Wilcoxon signed-rank test further confirmed the statistical significance of these improvements. The development of microlearning-based teaching materials resulted in various formats, with participants favoring text/image and game formats for their engagement and efficiency. Despite some limitations, video, flashcards, and audio podcasts improve student understanding and material delivery. The study emphasizes the potential of microlearning to solve educational difficulties and encourages the continuing development and improvement of these teaching materials to further support educators.